Formation mechanisms and functionality of boundary films derived from water lubricated polyoxymethylene/hexagonal boron nitride nanocomposites. (5th February 2017) - Gao, Chuanping; Guo, Guofan; Zhang, Ga; Wang, Qihua; Wang, Tingmei; Wang, Honggang
Abstract: Development of high-performance polymer composites exposed to water lubrication conditions is of increasing interests for numerous applications, where high durability and reliability are demanded. However, formation of a protective boundary reaction layer on the rubbing surfaces can be problematic with the presence of water. The roles of hexagonal boron nitride ( h -BN) nanoparticles on the tribological performance of polyoxymethylene (POM) and POM composite reinforced with short carbon fibers were investigated. It is identified that the addition of low loading h -BN greatly improves the tribological performance, e.g. wear resistance of POM is enhanced by one order of magnitude. Moreover, h -BN and carbon fibers play a synergetic role in enhancing the wear resistance. Tribo-chemistry and nanostructures of the boundary film were comprehensively investigated. It is revealed that H3 BO3 and B2 O3 generated as products of tribo-chemical reactions are arrayed in a closely packed outmost layer of the boundary film and exert an important influence on the tribological performance. Our work gives the evidence that the basal planes of H3 BO3 and B2 O3 are aligned parallel to the sliding direction, leading to low friction and wear. Graphical abstract: Highlights: The hydration of h -BN nanoparticles plays an important role to form a stable boundary film on the sliding contact surfaces. H3 BO3 and B2 O3 molecules are arrayed in a closely packed outmost layer of the boundary film. The basal planes of H3 BO3 and B2 O3 are aligned parallel to the sliding direction. The aligned H3 BO3 and B2 O3 basal planes are crucial for the high tribological performance of the POM nanocomposite.